Case study of an aboriginal community-controlled health service in Australia: Universal, rights-based, publicly funded comprehensive primary health care in action - Freeman, T.; Baum, F.; Lawless, A.; Labonté, R.; Sanders, D.; Boffa, John; Edwards, T.; Javanparast, S. (2016)
Universal health coverage provides a framework to achieve health services coverage but does not articulate the model of care desired. Comprehensive primary health care includes promotive, preventive, curative, and rehabilitative interventions and health equity and health as a human right as central goals. In Australia, Aboriginal community-controlled health services have pioneered comprehensive primary health care since their inception in the early 1970s. Our five-year project on comprehensive primary health care in Australia partnered with six services, including one Aboriginal community-controlled health service, the Central Australian Aboriginal Congress. Our findings revealed more impressive outcomes in several areas—multidisciplinary work, community participation, cultural respect and accessibility strategies, preventive and promotive work, and advocacy and intersectoral collaboration on social determinants of health—at the Aboriginal community-controlled health service compared to the other participating South Australian services (state-managed and nongovernmental ones). Because of these strengths, the Central Australian Aboriginal Congress’s community-controlled model of comprehensive primary health care deserves attention as a promising form of implementation of universal health coverage by articulating a model of care based on health as a human right that pursues the goal of health equity.